Design And Development Of Investment Management Website Based On Crowdfunding In Small And Medium-sized Enterprises Using Iterative And Incremental Method - Fauza Annisa; Nia Ambarsari; Taufik Nur Adi (eProceedings of Engineering, 2015)
Abstract Investment is all forms of investing activity, either by domestic investors or foreign investors to obtain businesses in the territory of the Republic of Indonesia. . In the category of venture capital investment, this kind of investment is tend to be needed as capital injections for society who want to build their own business or who have set up a business but still have less availability of capital for their businesses. One of the form of business which mostly need the capital injections is Small and Medium-sized Enterprises (SMEs). The development of an SME depends on several factors, such as the availability of capital, the use of technology to optimize production and market expansion. For capital issues, there are two main constraints often faced by SMEs. First, SMEs are having trouble in finding investors who are willing to invest in their businesses. This was due to the majority of SMEs do not have access to find and get detailed and relevant information about investors. Second, the complexity of the bureaucracy and a lot of administrative requirements that must be fulfilled if SMEs applied for a loan to the government, financial institutions, or banks. Two of these constraints inhibit SMEs in Indonesia to grow and compete with other competitors. To overcome those constraints will be built a website application of investment management based on crowdfunding using iterative and incremental method from the point of view of SMEs. The website will incorporate the investment management concept and crowdfunding model. Investment management concept will be used to regulate the procedure to be conducted by SMEs in order to obtain venture capital and how to refund to the investors. Crowdfunding model will be needed for SMEs to be able to choose and corporate with the appropriate investors because the model depends on the crowd to find and get the information and finding the solutions needed. Keywords: Investment Management, SMEs, Crowdfunding